Rethinking the humanism - Polo Santillán, Miguel Ángel (2016)
Humanism has been the subject of harsh criticism in the twentieth century as an expression of anti-modern attitude. Modern humanism affirms the intrinsic value of rational beings to the detriment of other beings who do not have that feature. However, we do not think it is necessary to get rid of humanism, but to extend its meaning, so it can dialogue with other aspects that define it. A definition of the human, especially closed, can bring discrimination and violence. Humanism, rather than being a definition of the human, should be a caring attitude of the human and of what allows it to be human.